Antimicrobial hydrogels for the treatment of infection. Issue 6 (November 2013) - Salomé Veiga, Ana; Schneider, Joel P.; Gierasch, Lila; Lynn, David; Schneider, Joel
ABSTRACT The increasing prevalence of microbial infections, especially those associated with impaired wound healing and biomedical implant failure has spurred the development of new materials having antimicrobial activity. Hydrogels are a class of highly hydrated material finding use in diverse medical applications such as drug delivery, tissue engineering, as wound fillers, and as implant coatings, to name a few. The biocompatible nature of many gels make them a convenient starting platform to develop selectively active antimicrobial materials. Hydrogels with antimicrobial properties can be obtained through the encapsulation or covalent immobilization of known antimicrobial agents, or the material itself can be designed to possess inherent antimicrobial activity. In this review we present an overview of antimicrobial hydrogels that have recently been developed and when possible provide a discussion relevant to their mechanism of action. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 637–644, 2013.